(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This paper investigates the existence and uniqueness of a solution to boundary value problems involving the Caputo fractional derivative in the Banach space. It is based on the application of topological degree approach and fixed-point theory with topological structures in some appropriate situations